Investigation of a novel dew point indirect evaporative air conditioning system for buildings - Duan, Zhiyin (2011)
This study aims to improve the performance of existing indirect evaporative coolers. A new dew point indirect evaporative cooler with counter-current heat/mass exchanger was developed in this research by optimal design, material selection, numerical simulation, experimental investigations and economic, environmental, regional acceptance analysis.